Crack growth analysis for rock-like materials with ordered multiple pre-cracks under biaxial compression - Wang, Min; Cao, Ping; Wan, Wen; Zhao, Yan-lin; Liu, Jie; Liu, Jing-shuo (Journal of Central South University, 2017)
The pre-burying iron sheets approach was used to prepare rock-like materials with ordered multiple pre-cracks. 60 specimens in total were prepared in these experiments. Through biaxial compression experiments, the influence of both the number of pre-cracks and pre-cracks angles to crack growth was analyzed. Meanwhile, species of rock bridge failure were summarized, namely, wing crack, secondary shear crack between horizontal pre-cracks and secondary shear crack between vertical pre-cracks. The wing crack plays a significant role in crack growth. Furthermore, fractal dimension was adopted to describe quantitatively the crack growth during the failure process. The results indicate that with the failure of specimens, corresponding fractal dimension for specimen monotonically increases, which indicates that the fractal dimension can be considered to the failure of the specimens quantitatively.